2021
DOI: 10.1093/rheumatology/keab146
|View full text |Cite
|
Sign up to set email alerts
|

Is fibromyalgia associated with a unique cytokine profile? A systematic review and meta-analysis

Abstract: Objectives The aetiology of primary chronic pain syndromes (CPS) is highly disputed. We performed a systematic review and meta-analysis aiming to assess differences in circulating cytokines levels in patients with diffuse CPS (fibromyalgia) versus healthy controls (HC). Methods Human studies published in English from the PubMed and MEDLINE/Scopus and Cochrane databases were systematically searched from inception up to January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 51 publications
2
51
2
Order By: Relevance
“…The presence of a common pathway mediated by immune dysregulation provides a common cause of these conditions, and IL-6 is elevated in these syndromes. 52 , 53 , 54 , 55 , 56 Interleukin 6 is associated with fatigue and sleep disturbance in chronic stress and inflammation in CS syndromes. 57 Diagnosis of these conditions has traditionally been frustrating as patients will have multiple disabling symptoms yet will have few (if any) abnormalities on laboratory and procedural testing.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a common pathway mediated by immune dysregulation provides a common cause of these conditions, and IL-6 is elevated in these syndromes. 52 , 53 , 54 , 55 , 56 Interleukin 6 is associated with fatigue and sleep disturbance in chronic stress and inflammation in CS syndromes. 57 Diagnosis of these conditions has traditionally been frustrating as patients will have multiple disabling symptoms yet will have few (if any) abnormalities on laboratory and procedural testing.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a common pathway mediated by immune dysregulation provides a common etiology of these conditions and IL-6 is elevated in these syndromes. [51][52][53][54][55] IL-6 is associated with fatigue and sleep-disturbance in chronic stress and inflammation in central sensitization syndromes. 56 Treatment of these conditions have traditionally been frustrating as patients will have multiple disabling symptoms yet will have very few (if any) abnormalities on laboratory and procedural testing.…”
Section: Discussionmentioning
confidence: 99%
“…All these previous works demonstrated that MAO-A inhibition was able to decrease ROS generation and the ROS-activated inflammatory process in particular through NF-κB pathway inhibition. Several studies showed that inflammatory cytokines in fibromyalgia patients could drive disturbances in neural networks during the interaction of the nervous system with immune cells, which eventually could lead to an increase in central and peripheral sensitization as well as neuroinflammation [23]. For all these reasons, the aim of this study was to investigate the therapeutic potential of metaxalone in an in vitro experimental paradigm of microglial cell inflammation (obtained through IL-1β stimulation) [24] that mimics the phenomenon of neuroinflammation involved in several neurological disorders, including fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%